Guidance and Counseling Methods from the Perspective of the Qur’an: Surah An-Nahl Verse 125 - Rustianti, Nora; Zaini, Hasan; Irman, Irman (The Future of Education Journal, 2025)
This paper is motivated by the desire to explore more deeply the methods of guidance and counseling as referred to in the Qur’an, Surah An-Nahl verse 125. This verse contains three main methods in the guidance and counseling process: the method of hikmah (wisdom), mau‘izhah hasanah (good advice), and mujādalah ahsan (debate in the best manner). This study employs a descriptive qualitative approach in the form of a literature review, aiming to explore the counseling values embedded in the verse and their relevance to modern counseling practices. The findings show that the guidance and counseling approach based on the Qur’an is not only relevant within an Islamic context but also holds universal value in character building, behavior transformation, and strengthening interpersonal relationships. This article recommends that these three methods continue to be developed within the scientific field of Islamic guidance and counseling, so they may serve as practical guidelines for Muslim counselors in providing services aligned with Sharia principles.